Construction of drug–drug conjugate supramolecular nanocarriers based on water-soluble pillar[6]arene for combination chemotherapy. Issue 68 (7th August 2018) - Shao, Wei; Liu, Xin; Sun, Guangping; Hu, Xiao-Yu; Zhu, Jun-Jie; Wang, Leyong
Abstract : Pillararene-based GSH-responsive drug–drug conjugate supramolecular prodrug nanocarriers have been successfully constructed for efficient combination chemotherapy. Abstract : The synergistic effect of two anticancer drugs can significantly overcome the multidrug resistance of tumor cells and improve the drug bioavailability. Herein, two different anticancer drugs, camptothecin and chlorambucil, are successfully connected together by a disulfide linkage to get a novel drug–drug conjugated prodrug (G ). Using water-soluble pillar[6]arene (WP6 ) as a host molecule, a supramolecular host–guest complexWP6 ⊃G is formed, which can further self-assemble into supramolecular vesicles in aqueous solution. In the specific microenvironment of cancer cells, the disulfide linkage is destroyed and the two anticancer drugs can be released efficiently to achieve a better synergistic effect than a single anticancer drug. Notably, these prodrug nanocarriers can not only effectively kill the cancer cells but also obviously reduce the undesirable side effects on normal cells.